2010
DOI: 10.1017/s1461145709991234
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced normalization of decreased BDNF serum concentration in elderly women with remitted major depression

Abstract: Major depression (MD) has been associated with decreased brain-derived neurotrophic factor (BDNF) serum levels, while antidepressant drugs were found to increase these decreased BDNF levels. We investigated if this is also caused by a single exercise session in elderly women with remitted MD. In our study 35 elderly women with a (partially) remitted depressive episode of unipolar depression according to DSM-IV criteria within the last year and 20 age-matched healthy female controls were included. Depression se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
112
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(120 citation statements)
references
References 37 publications
6
112
0
2
Order By: Relevance
“…Human studies on the effects of exercise-induced BDNF changes in depressed populations are still preliminary, although BDNF levels were transiently increased in elderly women with remitted major depression (Laske et al, 2010) and in unmedicated patients suffering from major depressive disorder (Gustafsson et al, 2009). …”
Section: Exercise and Its Effect On Neuroprogressionmentioning
confidence: 99%
“…Human studies on the effects of exercise-induced BDNF changes in depressed populations are still preliminary, although BDNF levels were transiently increased in elderly women with remitted major depression (Laske et al, 2010) and in unmedicated patients suffering from major depressive disorder (Gustafsson et al, 2009). …”
Section: Exercise and Its Effect On Neuroprogressionmentioning
confidence: 99%
“…Furthermore, the ability of these compounds to modulate neurotrophic factors such as BDNF makes them useful targets for the prevention of cognitive decline since these are crucial for neuronal survival and for the protection of neurons from injury (225) . BDNF levels are known to decline during aging and their levels have been shown to correlate with human learning and memory (226)(227)(228)(229) , which has driven a considerable amount of research into design drugs that target BDNF and regulate its endogenous levels in the brain (230) . Indeed, drugs used to prevent AD such as memantine, as well as newly developed therapeutic interventions, both target BDNF and its levels in brain regions affected by the disease (231)(232)(233) .…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%
“…Another study demonstrated that exercise and social contact both result in significant reductions in the total and the psychological subscale of the Beck Depression Inventory (BDI) [28]. These results indicate that short term exercise has a broader effect than control conditions in reducing symptoms of depression in moderately depressed elderly populations, but the precise mecha- [29]. The results of this study suggest that daily exercising contributes to a good mental condition, and the non-exercising subjects showed significant improvement in their mental condition by starting and continuing to exercise.…”
Section: Discussionmentioning
confidence: 99%